Ukrainian and japanese wooden architecture : convergent evolution (sacral architecture) - Shevtsova, Galyna (КНУБА, 2014)
. У статті досліджено специфічні аспекти аналогій давньої дерев’яної архітектури України і Японії, що дозволяє говорити про їх конвергентну (схожої через однакові умови розвитку) еволюцію, можливу через схожість похідних розвитку: клімату, сільськогосподарського типу культури та від початкових вірувань анімістичного типу. Перша частина статті була присвячена найбільш давнім періодам існування дерев’яної архітектури України і Японії та народному житлу. У другій частині розглянуто храмову архітектуру. The article deals with some special points of Ukrainian and Japanese ancient wooden architecture similarity pointing to the possibility of their convergent evolution. Such akin genesis could be possible because of initial developing circumstances (climate, the type of old agriculture culture, the type of prehistoric animistic beliefs) alikeness. The first part of the article was devoted to the early periods of Ukrainian and Japanese wooden architecture existence and also to the both countries rural houses architecture. The second part of the article is devoted to the Ukrainian and Japanese wooden temples similarity. Key words: wooden architecture, Ukraine, Japan, church, temple, shrine, genesis.
Keywords: wooden architecture; Ukraine; Japan; church; temple; shrine; genesis; дерев'яна архітектура; Україна; Японія; церква; буддійський храм; святилище синто; генеза; 726.1(477+520)